The Effect of Price Advantage, Product Advantage, and Technological Advantage, with Brand Image as an Intervening Variable, on Brand Trust in Rational Combi Ovens - Permana, Lucky; Efendi, Efendi; Kristiadi, Al. Agus (Journal Research of Social Science, Economics, and Management, 2026)
The purpose of this research was to test the influence of product quality, price perception and equity on consumers who are satisfied with the reliability of composite materials. This study uses a quantitative approach with a survey method. Data was collected from 200 respondents who were users of Rational Combi Oven through the distribution of questionnaires. The data analysis technique used is Structural Equation Modeling Partial Least Squares (SEM-PLS) with the help of SmartPLS 3.0 software to test the validity, reliability, structural model, and research hypothesis. The results of the study show that product excellence has a positive and significant effect on brand trust, while price perception and technological excellence do not have a significant effect on brand trust directly. Brand image has been proven to have a significant effect on brand trust. In addition, technological excellence has a significant effect on brand image, while price perception and product excellence have no significant effect on brand image. This research highlights the importance of quality control, competitive pricing strategies and consistent product design to improve customer satisfaction in the kitchen industry, especially Combi Oven cookware.